Equality and diversity in democracy: how can we democratize inclusively?. Issue 5 (20th June 2016) - Martinez Palacios, Jone
Abstract : Purpose: The purpose of this paper is to propose a theoretical framework for democratize inclusively through participatory and deliberative apparatus. Design/methodology/approach: The paper draws on literature from inclusion in deliberation, gender in participation and intersectionality to critically analyze the democratic deepening. By bringing into dialogue with one another "the norm of parity of participation" (Fraser, 2006), "communicative democracy" (Young, 1993) and the "matrix of domination" (Collins, 1990) a response to one of the questions that has been put to European and North American thought in democracy since the 1960s is proposed: how is it possible to democratize inclusively? Findings: The reproduction of domination through apparatuses for the extension of democracy is both possible and probable. So, to democratize inclusively, it is necessary to bring the theories on vertical and horizontal inclusion into dialogue with each other. With the aim of establishing a dialogue between the two, it is necessary to export complex thought regarding oppression and inequality into the design of deliberative and participatory apparatuses. For that, consider that designing democratization processes based on the fact that the intersectional experience of oppression is not an exception but rather an everyday occurrence allows participatory procedures to be made more inclusive. Practical implications: This paper proposes a tool designed with a focus on dialogue among the norm of parity of participation, communicative democracy and the matrix of oppression, based on 11 direct questions for the inclusive design of deliberative or participatory procedures. Facilitators, experts and social agents involved in deliberative or participatory processes will be able to use this question-based instrument in their work. Originality/value: This paper has applied value because it offers a conceptual key to the design of and thought about participatory inclusive processes. The originality of this approach lies in its shift away from partial analyses of horizontal and vertical inclusion. It is of use both to facilitators of participatory processes and educators and researchers concerned with democratization. It offers an instrument for working on reflexivity with regard to inclusion in democratic extension, based on a series of key questions that can be used as a checklist. In comparison with other forms of considering inclusion in democracy, the proposal considered includes complex thought on oppression based on the critique of simple identity, as well as on an intersectional perspective.